TRANSLATION SHIFT AND ITS ACCURACY IN INDONESIANENGLISH TRANSLATION OF PASUNG JIWA - Irine Mely Maryani; Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2021)
This research aimed at describing translation shifts and its accuracy that happen in IndonesianEnglishtranslationofnovelPasungJiwa.Translationshiftisthechangesthatoccurwhenatextistranslatedintoanotherlanguageduetoeitherthedifferencesbetweenthetwolanguagesorthetranslator’schoices.Inthisresearch,thewriterusesCatford’stheoryoftranslationshiftandNababan’stheoryofTranslationQualityAssessment.Thisresearchisconsideredasdescriptivequalitativeresearch. All of the data are in the form of words, phrases, and clauses which arefound in novel Pasung Jiwa and its translated version. Those data are taxonimized into fivedifferent types of translation shifts. The analysis shows that there are 331 shifts found in novel;level shift is 47 (14%), class shift is 27 (8%), structure shift is 93 (28%), unit shift is 103 (31%),and intra-system shift is 61 (19%). In term of accuracy, 154 data are considered accurate (46%),152 data are considered less accurate (46%), and 25 data are considered inaccurate (8%).Keywords: Translation shift, translation quality assessement, translation technique, translationaccuracy, translation shift in Pasung Jiwa